Pyroptosis, apoptosis, and autophagy are involved in infection induced by two clinical Klebsiella pneumoniae isolates with different virulence - Wang, Xueting; Bi, Chunxia; Xin, Xiaoni; Zhang, Mengmeng; Fu, Hengxia; Lan, Lei; Wang, Mengyuan; Yan, Zhiyong (Frontiers in Cellular and Infection Microbiology, 2023)
Klebsiella pneumoniae can cause widespread infections and is an important factor of hospital- and community-acquired pneumonia. The emergence of hypervirulent K. pneumoniae poses a serious clinical therapeutic challenge and is associated with a high mortality. The goal of this work was to investigate the influence of K. pneumoniae infection on host cells, particularly pyroptosis, apoptosis, and autophagy in the context of host–pathogen interactions to better understand the pathogenic mechanism of K. pneumoniae. Two clinical K. pneumoniae isolates, one classical K. pneumoniae isolate and one hypervirulent K. pneumoniae isolate, were used to infect RAW264.7 cells to establish an in vitro infection model. We first examined the phagocytosis of macrophages infected with K. pneumoniae. Lactate dehydrogenase (LDH) release test, and calcein-AM/PI double staining was conducted to determine the viability of macrophages. The inflammatory response was evaluated by measuring the pro-inflammatory cytokines and reactive oxygen species (ROS) production. The occurrence of pyroptosis, apoptosis, and autophagy was assessed by detecting the mRNA and protein levels of the corresponding biochemical markers. In addition, mouse pneumonia models were constructed by intratracheal instillation of K. pneumoniae for in vivo validation experiments. As for results, hypervirulent K. pneumoniae was much more resistant to macrophage-mediated phagocytosis but caused more severe cellular damage and lung tissues damage compared with classical K. pneumoniae. Moreover, we found increased expression of NLRP3, ASC, caspase-1, and GSDMD associated with pyroptosis in macrophages and lung tissues, and the levels were much higher following hypervirulent K. pneumoniae challenge. Both strains induced apoptosis in vitro and in vivo; the higher apoptosis proportion was observed in infection caused by hypervirulent K. pneumoniae. Furthermore, classical K. pneumoniae strongly triggered autophagy, while hypervirulent K. pneumoniae weakly activated this process. These findings provide novel insights into the pathogenesis of K. pneumoniae and may form the foundation for the future design of treatments for K. pneumoniae infection.